Lithuanian priests – saver of Jews - Sakaitė, Viktorija (Genocidas ir rezistencija, 2002)
The archive of the Rescue Department of the Jewish Vilna Gaon Museum of Jewish History has a list of more than 2,700 names of people who rescued Jews in Lithuania. It contains all the information gathered from various sources about the people we call righteous. It is information for long-term research work. Time is our enemy here: after all these years, it is very difficult to establish names, to verify the rescue situation, to know the fate of the rescuers and the rescued. There are 159 clergymen on this list.
Keywords: German occupation; Catholic priests; Holocaust; Redeemers